Towards dispersion relations for tapered core dielectric elliptical fibers - CHOUDHURY, P; KUMAR, D (ELSEVIER GMBH, 2007)
The paper presents an analytical investigation of the electromagnetic wave propagation in a tapered core dielectric elliptical step-index fiber. Implementing Maxwell's equations in elliptical coordinates, field components are deduced that essentially incorporate Mathieu and the modified Mathieu functions. Finally, the characteristic dispersion equations are developed for even and odd modes supported by the fiber. (C) 2006 Elsevier GmbH. All rights reserved.